2016
DOI: 10.1007/s00380-016-0895-x
|View full text |Cite
|
Sign up to set email alerts
|

Higher hemoglobin A1c levels are associated with impaired left ventricular diastolic function and higher incidence of adverse cardiac events in patients with nonischemic dilated cardiomyopathy

Abstract: We aimed to elucidate the relationship between glycated hemoglobin (HbA1c), cardiac systolic/diastolic function, and heart failure (HF) prognosis during guideline-directed medical therapy in patients with nonischemic dilated cardiomyopathy (NIDCM). We evaluated 283 hospitalized NIDCM patients, who were grouped according to baseline (BL) and 1-year (1Y) levels of HbA1c (<6.0, 6.0-6.9, and ≥7.0 %). The primary endpoint was defined as either readmission for HF worsening or cardiac death. Approximately half of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…More importantly, the relationship between HbA1c and HF has been reported in NIDCM patients as well. A previous study reported that poor glycemic control may increase the risk of subsequent HF events in NIDCM patients [ 31 ]. In the current study, our data showed that an increased HbA1c is associated with decreased LV strains, and this association is more prominent in NIDCM patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, the relationship between HbA1c and HF has been reported in NIDCM patients as well. A previous study reported that poor glycemic control may increase the risk of subsequent HF events in NIDCM patients [ 31 ]. In the current study, our data showed that an increased HbA1c is associated with decreased LV strains, and this association is more prominent in NIDCM patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariable linear regression analysis showed that HbA1c was an independent determinant of LV global radial and longitudinal peak strain in NIDCM patients with T2DM. Similarly, Ikeda et al found that hyperglycemic is a risk factor for the progression of concomitant abnormal LV relaxation during follow-up, resulting in poor prognosis in patients with NIDCM [ 31 ]. Another study confirmed this change in myocardial relaxation by cardiac catheterization in patients with DM-complicated NIDCM [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of 14 studies are summarized in Table 1. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] Six studies evaluated primarily patients who were taking antidiabetic medications, while eight studies described findings in patients who were largely not taking such drugs, either because they had not been diagnosed with diabetes or because their diabetes was being treated only with dietary measures. In each of the eight studies that evaluated patients who were generally not receiving glucose-lowering drugs, the risk of death was not increased in patients with a baseline value…”
Section: Resultsmentioning
confidence: 99%
“…The findings of 14 studies are summarized in Table . Six studies evaluated primarily patients who were taking antidiabetic medications, while eight studies described findings in patients who were largely not taking such drugs, either because they had not been diagnosed with diabetes or because their diabetes was being treated only with dietary measures.…”
Section: Resultsmentioning
confidence: 99%
“…Although current guidelines recommend a target level of HbA1c < 7% in type 2 DM patients 6 , some trials proved that HbA1c could independently predict mortality with U-shaped relationship and the lowest mortality HbA1c range was 6.5-7.9% 7,8 , while other trials showed a direct relationship with HbA1c < 6.5% or inverse relationship with HbA1c ≥ 8.7%. 9,10 Furthermore, Lejeune et al 11 demonstrated HbA1c > 7% was protective for patients following heart failure with preserved ejection fraction, whereas some trials indicated HbA1c > 7% was associated with higher rate of adverse outcomes, including mortality, for patients following heart failure with reduced ejection fraction 12,13 , which means the effect of different HbA1c levels on adverse outcomes may be various in response to the types of heart failure. In spite of accumulating evidence, there are no further pooled analysis to gure out what HbA1c levels should be controlled for heart failure patients with pre-DM or non-DM.…”
Section: Introductionmentioning
confidence: 99%